Arterial Applanation Tonometry: Feasibility and Reproducibility in Children and Adolescents - Lowenthal, Alexander; Evans, Jasmine M.A.; Punn, Rajesh; Nourse, Susan E.; Vu, Chau N.; Popat, Rita A.; Selamet Tierney, Elif Seda (American journal of hypertension, 2014)
BACKGROUND Aortic pulse wave velocity (PWV) and augmentation index (AIx) are markers of vascular health and have recently been used in pediatric clinical trials. However, there are limited data on standardization of these measurements in pediatrics. The objective of this study was to prospectively test the feasibility and reproducibility of PWV and AIx in children and adolescents. METHODS We performed arterial tonometry on 2 different days within 2 weeks in 40 healthy subjects aged 10-19 years. PWV and AIx were measured in triplicate on each visit. RESULTS The visits were separated by a mean of 3.08±3.7 days. We obtained PWV in 77 of 80 (96%) visits and AIx in 76 of 80 (95%) visits in triplicate. Intraclass correlation coefficients (ICCs) for PWV were 0.61 (95% confidence interval (CI) = 0-0.86) when at least 2 measurements and 0.92 (95% CI = 0-1) when 3 measurements were obtained at each visit that met the quality criteria established for adults by the manufacturer (n = 17 and 3 paired visits, respectively). For AIx, ICCs were 0.78 (95% CI = 0.58-0.88) and 0.81 (95% CI = 0.63-0.90) when measurements with an operator index ≥80, a measure of the quality of the waveform, were included (n = 39 and 36 paired visits, respectively). CONCLUSIONS Arterial applanation tonometry is feasible and reproducible in healthy children and adolescents. AIx has excellent intervisit reproducibility, whereas the intervisit reproducibility of PWV relies on acquisition of multiple measurements that meet quality criteria established for adults. These results have implications for the methodology of future pediatric clinical trials in a population at increasingly higher risk for premature atherosclerosis.